2020
DOI: 10.1002/mgg3.1132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic data of 22 new patients with SMAD3 pathogenic variants and review of the literature

Abstract: BackgroundPathogenic SMAD3 variants are responsible for a cardiovascular phenotype, mainly thoracic aortic aneurysms and dissections. Precocious identification of the vascular risk such as aortic dilatation in mutated patients has a major impact in terms of management, particularly to avoid dissection and sudden death. These vascular damages are classically associated with premature osteoarthritis and skeletal abnormalities. However, variable expressivity and incomplete penetrance are common with SMAD3 variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In particular, Loeys-Dietz syndrome type 3 (LDS3), originally named aneurysms-osteoarthritis syndrome because of the striking findings of early-onset osteoarthritis in the fourth decade of life and the presence of aortic and other vascular aneurysms, is typically considered milder than LDS1/2. While similar systemic manifestations can be present in LDS3 patients as compared to LDS1/2 patients, the of age of onset of vascular pathology is usually later (Chesneau et al, 2020;Schepers et al, 2018;van de Laar et al, 2011) and 34.8 years, respectively, which is nearly a decade before the onset of aortic events in LDS3 individuals (Jondeau et al, 2016). And although not seen in the MAC, aortic dilation necessitating surgical repair has been described in pediatric patients with SMAD3-related Loeys-Dietz syndrome (Chesneau et al, 2020;Fitzgerald, Bhat, Conard, Hyland, & Pizarro, 2014), with the youngest reported age of aneurysm repair at 12 months old (Wischmeijer et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In particular, Loeys-Dietz syndrome type 3 (LDS3), originally named aneurysms-osteoarthritis syndrome because of the striking findings of early-onset osteoarthritis in the fourth decade of life and the presence of aortic and other vascular aneurysms, is typically considered milder than LDS1/2. While similar systemic manifestations can be present in LDS3 patients as compared to LDS1/2 patients, the of age of onset of vascular pathology is usually later (Chesneau et al, 2020;Schepers et al, 2018;van de Laar et al, 2011) and 34.8 years, respectively, which is nearly a decade before the onset of aortic events in LDS3 individuals (Jondeau et al, 2016). And although not seen in the MAC, aortic dilation necessitating surgical repair has been described in pediatric patients with SMAD3-related Loeys-Dietz syndrome (Chesneau et al, 2020;Fitzgerald, Bhat, Conard, Hyland, & Pizarro, 2014), with the youngest reported age of aneurysm repair at 12 months old (Wischmeijer et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…In particular, Loeys‐Dietz syndrome type 3 (LDS3), originally named aneurysms‐osteoarthritis syndrome because of the striking findings of early‐onset osteoarthritis in the fourth decade of life and the presence of aortic and other vascular aneurysms, is typically considered milder than LDS1/2. While similar systemic manifestations can be present in LDS3 patients as compared to LDS1/2 patients, the of age of onset of vascular pathology is usually later (Chesneau et al, 2020; Schepers et al, 2018; van de Laar et al, 2011). Hostetler et al (2019) reported data from the Montalcino Aortic Consortium (MAC) indicating that of 212 individuals with SMAD3 mutations, only 37% had ever experienced an aortic event (defined as elective aortic aneurysm repair, aortic dissection, or aortic rupture) with a median age at first aortic event of 47 years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result, it is generally accepted that SMAD3 variants are characterized by inter‐ and intra‐familial variability in phenotypic expression in addition to incomplete penetrance. Moreover, some patients present vascular aneurysms or dissections of small arteries without an aortic phenotype (Chesneau et al., 2020; Hostetler et al, 2019). The absence of complete arterial tree imaging in some of our patients makes characterization of a definitive clinical phenotype rather difficult.…”
Section: Discussionmentioning
confidence: 99%